FOREIGN POLICY AND PRIORITIES OF THE REPUBLIC OF SOUTH KOREA IN THE LATE 20TH AND EARLY 21ST CENTURIES - Urunov Xasan Rayimovich (Modern American Journals, 2025)
The diplomatic negotiations that began between the victorious and defeated countries after the end of World War II reflected a political reality that, in a sense, would decide the future fate of the world's countries. The "Cold War" that began between the two giants of the world posed the question of which country to stand on in front of the remaining countries. The world became bipolar. Although the Korean Peninsula is a single nation, two states have been formed: the Republic of South Korea and the Democratic People's Republic of Korea (DPRK). In terms of foreign policy, the South Korean government was led by pro-American officials until the beginning of the 21st century, while the DPRK was led by a pro-Soviet leader. The issue under consideration is about the priorities and essence of South Korea's foreign policy in recent times.
Keywords: Global, conservative, ASEAN, president, northeast Asia, autonomy, strategy, USA, cold war, September 11, 2001, regionalism